2018
DOI: 10.1111/ijlh.12927
|View full text |Cite
|
Sign up to set email alerts
|

The association of HBG2, BCL11A, and HMIP polymorphisms with fetal hemoglobin and clinical phenotype in Iraqi Kurds with sickle cell disease

Abstract: It was demonstrated that SNPs in all three major HbF QTLs contribute significantly to HbF and clinical variability in Iraqi Kurds with SCD and that the cumulative number of minor alleles at contributing SNPs may serve as a better predictor of such variability in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…This is in contrast to several earlier series of patients with SCD not treated with hydroxyurea that carry rs7482144 in the γ-globin promoter. These patients were characterized by increased HbF levels 9,22,32,33 and, in contrast to our findings, also less frequent vasoocclusive events 1, [34][35][36][37] . Studies on the association of rs7482144 with complications of SCD in patients treated with hydroxyurea are scarce 38 .…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to several earlier series of patients with SCD not treated with hydroxyurea that carry rs7482144 in the γ-globin promoter. These patients were characterized by increased HbF levels 9,22,32,33 and, in contrast to our findings, also less frequent vasoocclusive events 1, [34][35][36][37] . Studies on the association of rs7482144 with complications of SCD in patients treated with hydroxyurea are scarce 38 .…”
Section: Discussioncontrasting
confidence: 99%
“…El‐Hazmi et al described the genotypes and phenotypes of SCD in the Arab population in 2011 8 . Since then, there have been many new studies describing variants of SCD genotypes and phenotypes, and with the emerging era of gene therapy for SCD, it is essential to compile the current evidence, especially in the last 5 years 22‐44 . We will pool all data describing the genotypic and phenotypic variants of SCD in the Arab population to date in a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cumulative numbers of minor alleles of these polymorphisms were positively linked to hemoglobin concentration but negatively so to LDH, reticulocyte counts, leukocyte counts, transfusion, and pain frequencies. The study concluded that the cumulative number of minor alleles at the three aforementioned polymorphisms may serve as a better predictor of phenotypic variability of SCD, than each one on its own (Al-Allawi et al 2019).…”
Section: Molecular and Clinical Aspects Of Sickle Cell Disease Among Iraqi Kurdsmentioning
confidence: 97%
“…One of the major modifiers of disease severity in SCD is hemoglobin F; the latter is modulated mainly by three major quantitative trait loci (QTL) on chromosomes 11, 2, and 6 (Thein et al 2009). A recent study enrolled 128 Kurdish SCD patients to address the role of these QTLs in the phenotypic variability of this disorder (Al-Allawi et al 2019). The study documented that HBG2 rs7482144, BCL11A rs1427407, and HMIP rs9399137 contributed significant 18.1%, 14.3%, and 8.8% to HbF variability in Kurdish Iraqi SCD.…”
Section: Molecular and Clinical Aspects Of Sickle Cell Disease Among Iraqi Kurdsmentioning
confidence: 99%